Preparation and Characterization of Advanced Nano medicine For Malaria: Box Behnken Design Approach: Pharmaceutical Science-Pharmaceutics - G. More, Anuradha; R. Potbhare, Parag; S. Kore, Padmaja; D. Chaudhari, Praveen; U. Kshirsagar, Pratiksha; R. Baheti, Radhika; C. Gupta, Surbhi (International Journal of Life Science and Pharma Research, 2022)
In tropical countries, malaria is a larger cause of sickness and death in adults and children. Drug resistance with antimalarial therapy has now become a serious problem worldwide and it is the basic reason for the need of combination therapy. Artemisinin-based combination therapy (ACT) is widely used nowadays. The drugs selected for the study from ACT were an Artesunate (AST) and Lumefantrine (LUM). In this study, the optimized Solid-Self nanoemulsifying drug delivery system (S-SNEDDS) formulation of AST and LUM was developed using Box Behnken design (BBD) which showed greater in-vitro drug release when compared to marketed formulation. Both the drugs AST and LUM show high solubility in Anise oil, Tween 80 (surfactant), and PEG 400 (co-surfactant). Ternary phase diagrams were used to select nanoemulsifying regions. It was found to have a maximum nanoemulsion region with a 2:1 surfactant to co-surfactant ratio. The effect of formulation variables was studied by BBD. Thirteen formulations were prepared and were further characterized based on globule size, PDI, zeta potential, self-emulsification time, cloud point, % transmittance and in vitro dissolution profiles. The optimized Liquid-SNEDDS (LSNEDDS) with RHLB 13.76 gives globule size (82.8 nm), % T (96.7 %), in vitro release of AST (98.4 %) and LUM (97.07%) at 45 min. was converted into S-SNEDDS by using neusilin US2 as an adsorbent. The S-SNEDDS was characterized by SEM, globule size (98.24 nm), % T (95.02 %), in vitro release of ART (95.18 %) and LUM (96.4%) at 45 min. DSC and FTIR study for S-SNEDDS assure that there was an absence of any chemical interaction within the drug and carrier. SEM, X-ray diffraction studies confirmed that drugs exist in amorphous nature. The present research successfully developed S-SNEDDS for bioavailability enhancement of AST and LUM in fix dose combination